2014
DOI: 10.1149/06138.0001ecst
|View full text |Cite
|
Sign up to set email alerts
|

NF3/NH3 Dry Cleaning Mechanism Inspired by Chemical and Physical Surface Modification of Si, SiO2, and Si3N4

Abstract: To understand the NF3/NH3 dry cleaning mechanism, we have investigated the dry cleaning process with different Si-based materials, Si, SiO2, and Si3N4 using atomic force microscopy (AFM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and x-ray photoelectron spectroscopy (XPS) in terms of surface modification. In this paper, we report that the NF3/NH3 dry cleaning process using down-flow plasma technique can cause significant surface modification on SiO2 depending on the NF3:NH3 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In the case of the Si 3 N 4 , the film loss thickness was much lower than SiO 2 and the removal selectivity (>30) could be obtained. In the case of NF 3 /NH 3 , similar to the results from previous researches [17], the highest SiO 2 film loss thickness could be obtained at the NF 3 /NH 3 (1:2) gas ratio but the film loss thickness was lower than that obtained with OF 2 / NH 3 chemistry. For NF 3 /NH 3 chemistry, the removal selectivity over Si 3 N 4 was also less than 20, therefore, the OF 2 /NH 3 chemistry exhibited better dry cleaning efficiency compared to the NF 3 /NH 3 chemistry.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the case of the Si 3 N 4 , the film loss thickness was much lower than SiO 2 and the removal selectivity (>30) could be obtained. In the case of NF 3 /NH 3 , similar to the results from previous researches [17], the highest SiO 2 film loss thickness could be obtained at the NF 3 /NH 3 (1:2) gas ratio but the film loss thickness was lower than that obtained with OF 2 / NH 3 chemistry. For NF 3 /NH 3 chemistry, the removal selectivity over Si 3 N 4 was also less than 20, therefore, the OF 2 /NH 3 chemistry exhibited better dry cleaning efficiency compared to the NF 3 /NH 3 chemistry.…”
Section: Resultssupporting
confidence: 88%
“…However, the remote plasma cleaning method has the potential to minimize surface damage due to the absence of ion bombardment and to have high-cleaning selectivity in the nanoscale pattern because the remote plasma cleaning generates plasmas at a separate location and introduces only dissociated radicals on the substrate surface [11]. The remote plasma cleaning of silicon dioxide (SiO 2 ) using the various gas combinations has been widely investigated to reduce surface damages and to have the high-cleaning selectivity over silicon nitride (Si 3 N 4 ) and, among the various compound gases using F-based gas/Hbased gas mixtures such as NF 3 /H 2 [12], SF 6 /H 2 O [13], NF 3 / H 2 O [14], NF 3 /NH 3 [15][16][17], NF 3 /NH 3 gas mixtures were the most frequently used. To clean the SiO 2 surface using NF 3 / NH 3 plasma, after the exposure of SiO 2 surface to the NF 3 / NH 3 mixture, the compound formed by the reaction of SiO 2 with NF 3 /NH 3 was desorbed by a heated showerhead at the same process chamber [15,16] or using separate chambers for the reaction of NF 3 /NH 3 plasma and desorption of the reacted compound [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that NH 4 F and HF reactants are formed in the NH 3 /NF 3 remote plasma chamber by NF 3 (respectively NH 3 ) dissociation into NF x (x = 1-2) and F [respectively NH x (x = 1-2) and H] and subsequent recombination of these fragments together and with the feed gases, as described by Eqs. ( 2)-( 5), 17,[23][24][25]…”
Section: Discussion On the Etching Mechanisms Of Si 3 N 4 Films Exposed To Nh 3 /Nf 3 Remote Plasmamentioning
confidence: 99%
“…It has already been reported that the etching of Si 3 N 4 or SiO 2 films exposed to NH 3 /NF 3 remote plasma proceeds with the formation of an ammonium hexafluorosilicate (NH 4 ) 2 SiF 6 salt layer on their surface. 17,[23][24][25] Figures 2(a) and 2(b) show the scanning electronic microscopy (SEM) and atomic force microscopy (AFM) images of the salt layer formed on a Si 3 N 4 film exposed to the NH 3 /NF 3 RP process at 60 °C. It looks like a tangle of polycrystals separated with cracks and voids.…”
Section: Kinetic Ellipsometrymentioning
confidence: 99%